Enhancing Psychiatric Care for Older Adults in a Care Home Setting: A Quality Improvement Project - Alex Milone; Yasir Hameed; Trish Phiri; Peace Ayodele (BJPsych Open, 2025)
Aims: The aims of the project were (i) to enhance collaboration between the multidisciplinary team working with people living with dementia such as the carers, general practitioners, pharmacists, mental health professionals and patients` families; (ii) improve the Community Mental Health Team (CMHT) response to referrals; (iii) reduce unnecessary referrals; (iv) provide psychiatric training to primary care colleagues; (v) reduce care home visits; (vi) reduce polypharmacy, especially antipsychotics in dementia; and (vii) increase the use of memory medications for dementia patients where indicated.